HISTORY OF ARCHAEOLOGICAL RESEARCH AT BRONZE AGE VILLAGE SETTLEMENT IN UZBEKISTAN (TAMADDUN NURI JURNALI, 2025)
Turon, Ustyurt, Chirchik-Ohangaron, Fergana, Zarafshan, Kashkadarya, Surkhandarya, Lower Amudarya, Yesen 1, 2, Karakuduq, Churuk, Ijond, Vaush.